The Relationship Between Baby Massage and The Sleep Quality of Babies Aged 3-6 Months at Pmb Midwifery Dian Armiati, A.Md.Keb Karangrejo Gempol District Pasuruan 2023 - Anin Andriyani (Kirana Publisher (KNPub), 2024)
Infancy is a golden period and this period cannot be repeated because this period comes very quickly, it is also called a critical period because babies are very sensitive to their environment, need proper nutrition and good stimulation to support their growth and development. At this time, the baby's brain is still developing. Babies are fragile individuals and require some adjustment. Babies experience difficulties in the adjustment process affecting their development and causing unpredictable behavior, the most fatal consequence of which is death. The sense of touch is very important in a baby's early life to help him adapt to his environment. Baby massage is an activity suitable for babies that helps improve the quality of sleep in babies, motor development in babies and fine motor skills in babies. At PMB Dian Armiati A.Md.Keb, Karangrejo Village, Gempol District, there are several independent practice places for midwives (PMB) but not all PMBs carry out baby massage which is carried out by midwives, namely at PMB Dian Armiati A.Md.Keb, Karangrejo Village, Gempol District .To determine the relationship between the influence of baby massage on the quality of baby sleep in PMB Dian Armiati A.Md.Keb, Karangrejo Village, Gempol District. With a cross sectional research design using the Wilcxon test method. This research is quantitative using an analytical survey method where researchers try to explore how and why health phenomena occurthe 30 respondents, it was found that before the baby massage was carried out, the majority of sleep quality was in the poor category, 18 babies (60%), after the baby massage, the sleep quality was in the good category, 20 babies (66.7%), so it can be concluded There is a relationship between baby massage and the quality of baby sleep